The Impact of The Acceptance of The Quick Response Code Indonesian Standard on Changes in Consumption Patterns at the Lappa Fish Auction Place in Sinjai Regency - Chakti, Andi Gunawan Ratu; Kamaruddin, Syamsu A.; Adam, Arlin (Postgraduate Bosowa University, 2025)
This study aims to evaluate the impact of QRIS (Quick Response Code Indonesian Standard) adoption on community consumption patterns in Sinjai Regency. The background of this research is the government's push to promote non-cash transactions via QRIS since 2019, but its adoption in areas with a traditional market economy base and MSMEs remains low. The method used is a mixed-method approach, comprising a quantitative survey of 31 traders and 67 consumers at the Lappa Fish Auction Place, Sinjai Regency, as well as semi-structured interviews to capture socio-cultural and technical barriers. The results show that only 11% of traders have activated QRIS, with an average of 2.5 non-cash transactions per day, while 15% of consumers have shifted to digital payments. Main obstacles include limited digital literacy, lack of trust in data security, and a habitual preference for cash. Digital sociology analysis reveals that limited social networks and reliance on old habits slow the diffusion of this innovation, resulting in an income gap approximately 12% higher for QRIS-using traders. The research recommendations include community-based digital literacy training, improved internet infrastructure in markets, and cross-stakeholder collaboration to promote financial inclusion and accelerate local digital transformation